1998
DOI: 10.1007/s002130050608
|View full text |Cite
|
Sign up to set email alerts
|

CP-154,526, a selective, non-peptide antagonist of the corticotropin-releasing factor 1 receptor attenuates stress-induced relapse to drug seeking in cocaine- and heroin-trained rats

Abstract: We have found that peptide antagonists of corticotropin-releasing factor (CRF) receptors attenuate reinstatement of heroin and cocaine seeking induced by footshock. Here we examined the effect of a nonpeptide, selective CRF1 receptor antagonist, CP-154,526, on reinstatement of heroin and cocaine seeking induced by footshock. Rats were trained to self-administer heroin or cocaine (0.1 and 1.0 mg/kg per infusion, i.v., respectively) for 9-12 days. Extinction sessions were given for up to 14 days, during which sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
159
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(178 citation statements)
references
References 22 publications
14
159
4
Order By: Relevance
“…It is well established that the activation of central CRF system is essential for stress-induced reinstatement of drug-seeking behavior (Shaham et al, 1997;Le et al, 2000;Shalev et al, 2006), and CRF receptor antagonism blocks this stress effect (Shaham et al, 1998). Identifying the BNST as a key structure for mediating this phenomenon, Erb and Stewart reported that stress-induced reinstatement of drugseeking behavior is mimicked by an intra-BNST injection of CRF and blocked by an intra-BNST injection of a CRF antagonist, D-Phe CRF (Erb and Stewart, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the activation of central CRF system is essential for stress-induced reinstatement of drug-seeking behavior (Shaham et al, 1997;Le et al, 2000;Shalev et al, 2006), and CRF receptor antagonism blocks this stress effect (Shaham et al, 1998). Identifying the BNST as a key structure for mediating this phenomenon, Erb and Stewart reported that stress-induced reinstatement of drugseeking behavior is mimicked by an intra-BNST injection of CRF and blocked by an intra-BNST injection of a CRF antagonist, D-Phe CRF (Erb and Stewart, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although SAinduced increases in plasma CORT were less pronounced than those evoked by EFS, the observed elevation of CORT in the absence of increased SA provides further evidence that elevated CORT alone is insufficient to produce escalation and suggests that CORT is exerting its permissive effects on neurobiological systems that are directly responsive to stressors and not cocaine. Although it is not clear exactly which glucocorticoid-dependent stressor-responsive target is responsible for the escalating effects of EFS, a strong case can be made for corticotropin releasing factor (CRF), which has been identified as a mediator of EFSinduced but not cocaine-induced reinstatement of extinguished cocaine-seeking behavior Shaham et al, 1998 andsee Sarnyai et al, 2001 for review).…”
Section: Discussionmentioning
confidence: 99%
“…The HPA axis hyper-responsivity to metyraponeinduced removal of glucocorticoid negative feedback in the present study suggests that endogenous opioidergic dysfunction may be involved in the mechanism of perpetuation of, and relapse to, cocaine addiction, and reinforces lines of inquiry into novel pharmacological treatments. Corticotropin-releasing factor antagonists have been demonstrated to attenuate stress-induced drug-seeking behavior (Shaham et al 1998) as well as IV cocaine self-administration (Goeders and Guerin 1998) in animal models. In addition, kappa opioid agonists, which may be acting to modulate cocaine-associated alterations in dopaminergic function, as well as alterations in HPA axis function, have been shown to affect cocaine self-administration and reinstatement of self-administration stimulated by cocaine exposure after a period of abstinence (Schenk et al 1999).…”
Section: Discussionmentioning
confidence: 99%